2020
DOI: 10.21608/geget.2021.39271.1013
|View full text |Cite
|
Sign up to set email alerts
|

Psychological assessment in children with chronic kidney disease on regular hemodialysis

Abstract: Introduction: Interestingly, health care professionals have the tendency to focus on the biological dimension of the disease or other technical issues related to hemodialysis machine and usually underestimate symptoms from mental sphere. Encouraging patients to express their feelings and addressing their psychological needs may be an essential measure to confront with this debilitating disease. Aim of Study: The objective of our study were to assess the presence, possible factors related and consequences of ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The number of cases and deaths in intensive care units due to AKI has grown from 5% to 30%, relative to other diseases. Despite technical advances in clinical treatment, acute nephritis-related deaths remain high as the practitioner can only give preventive care such as hemodialysis due to elevated amounts of creatine in the blood 14 . In general, several studies have found that CI-AKI and possibly AKI have declined in patients who have undergone heart surgery over the past 10 years, with the exception of those who had postoperative coronary angiography and tested positive for AKI that required dialysis (AKI-D) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The number of cases and deaths in intensive care units due to AKI has grown from 5% to 30%, relative to other diseases. Despite technical advances in clinical treatment, acute nephritis-related deaths remain high as the practitioner can only give preventive care such as hemodialysis due to elevated amounts of creatine in the blood 14 . In general, several studies have found that CI-AKI and possibly AKI have declined in patients who have undergone heart surgery over the past 10 years, with the exception of those who had postoperative coronary angiography and tested positive for AKI that required dialysis (AKI-D) 15 .…”
Section: Introductionmentioning
confidence: 99%